Socio-Cultural Determinants of Halal Consumption: A Comparative Study of Indonesia, Malaysia, and Nigeria - Akmal, Huriyatul; Binti Yusof, Nabilah (MD Research Center, 2025)
The halal industry has experienced significant growth in various countries with large Muslim populations, especially Indonesia, Malaysia, and Nigeria. This study aims to understand how the social and cultural characteristics of societies in these three countries influence consumer behavior toward halal products. Using a qualitative approach based on literature review, this research analyzes factors shaping halal consumption patterns, including infrastructure readiness, social inequality, and economic factors in each country. The findings reveal that although all three countries have high demand for halal products, there are significant differences in acceptance and adoption. In Indonesia and Malaysia, the halal industry is more advanced, supported by strong government policies, whereas in Nigeria, infrastructural challenges and inadequate regulations are major obstacles. The study also highlights that the public's understanding of halal extends beyond food to sectors such as cosmetics, pharmaceuticals, and Islamic finance. Consequently, this research provides important contributions to the development of more inclusive halal industry policies and marketing strategies tailored to the social and cultural contexts of each country. However, the study is limited by the use of secondary data, and further research involving direct interviews with consumers and stakeholders in these countries is highly recommended.